2014
DOI: 10.1371/journal.pone.0097746
|View full text |Cite
|
Sign up to set email alerts
|

X Chromosome-Linked CNVs in Male Infertility: Discovery of Overall Duplication Load and Recurrent, Patient-Specific Gains with Potential Clinical Relevance

Abstract: IntroductionSpermatogenesis is a highly complex process involving several thousand genes, only a minority of which have been studied in infertile men. In a previous study, we identified a number of Copy Number Variants (CNVs) by high-resolution array-Comparative Genomic Hybridization (a-CGH) analysis of the X chromosome, including 16 patient-specific X chromosome-linked gains. Of these, five gains (DUP1A, DUP5, DUP20, DUP26 and DUP40) were selected for further analysis to evaluate their clinical significance.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
0
16
0
9
Order By: Relevance
“…DUP1A, instead, was found exclusively and at a significantly higher frequency in patients. This gain fully duplicates a long non-coding RNA (LINC00685) that potentially acts as a negative regulator of a gene with potential role in spermatogenesis, PPP2R3B; according to our hypothesis, the mechanism by which DUP1A could lead to spermatogenic failure is a misbalanced ratio of the PPP2R3B and its antisense, causing a decrease in PPP2R3B transcription in the developing germ cells (Chianese et al 2014). Our data together with the identification of two SCOS patients with a duplication disrupting the PPP2R3B gene (Tü ttelmann et al 2011) indicate that CNVs mapping into this region and affecting either PPP2R3B or the long non-coding RNA (LINC00685) are good mutational targets for future case-control studies.…”
Section: R168 C Krausz and Othersmentioning
confidence: 76%
See 2 more Smart Citations
“…DUP1A, instead, was found exclusively and at a significantly higher frequency in patients. This gain fully duplicates a long non-coding RNA (LINC00685) that potentially acts as a negative regulator of a gene with potential role in spermatogenesis, PPP2R3B; according to our hypothesis, the mechanism by which DUP1A could lead to spermatogenic failure is a misbalanced ratio of the PPP2R3B and its antisense, causing a decrease in PPP2R3B transcription in the developing germ cells (Chianese et al 2014). Our data together with the identification of two SCOS patients with a duplication disrupting the PPP2R3B gene (Tü ttelmann et al 2011) indicate that CNVs mapping into this region and affecting either PPP2R3B or the long non-coding RNA (LINC00685) are good mutational targets for future case-control studies.…”
Section: R168 C Krausz and Othersmentioning
confidence: 76%
“…In fact, the two variants DUP1a and CNV69 were objects of large follow-up studies, together with other recurrent deletions, CNV67 and CNV64 (Chianese et al 2014, Lo Giacco et al 2014b. The first study analyzed three recurrent deletions (frequency O1%) in a large case-control setting (nZ1255) for their exclusive (CNV67) and prevalent (CNV64 and CNV69) presence in patients.…”
Section: R168 C Krausz and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, genome-wide CNV analyses in infertile men are thus far only performed in research settings (10,85,86,87), of which some have focused specifically on the X chromosome (88,89,90). When comparing infertile (oligo-or azoospermic) with fertile (or normozoospermic) men, the consistent finding of the available studies is a significantly higher overall 'burden' of microdeletions, especially on the sex chromosomes (10,85,88,89). In addition, one study has reported an increase of single nucleotide variations (SNVs) in infertile men compared with controls (10), and it has been speculated that infertility may be associated with an increased overall genome instability.…”
Section: X-chromosomal Deletionsmentioning
confidence: 99%
“…Исследование вариаций числа копий при нарушении репродуктивной функции В последние годы начато активное исследование микроструктурных перестроек хромосом, CNV, в том числе при различных формах нарушения развития и функции органов мужской и женской репродуктивной системы, при бесплодии и невынашивании беременно-сти, а также для детекции (скрининга) хромосомных му-таций у эмбриона до его имплантации и у плодов при потере беременности [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: секвенирование нового поколенияunclassified